Strategies for Promotion of a Healthy Lifestyle in Clinical Settings: Pillars of Ideal Cardiovascular Health: A Science Advisory From the American Heart Association. Issue 24 (25th October 2021) - Kris-Etherton, Penny M.; Petersen, Kristina S.; Després, Jean-Pierre; Anderson, Cheryl A.M.; Deedwania, Prakash; Furie, Karen L.; Lear, Scott; Lichtenstein, Alice H.; Lobelo, Felipe; Morris, Pamela B.; Sacks, Frank M.; Ma, Jun
Abstract : Engagement in healthy lifestyle behaviors is suboptimal. The vast majority of the US population does not meet current recommendations. A healthy lifestyle is defined by consuming a healthy dietary pattern, engaging in regular physical activity, avoiding exposure to tobacco products, habitually attaining adequate amounts of sleep, and managing stress levels. For all these health behaviors there are well-established guidelines; however, promotion in clinical settings can be challenging. It is critical to overcome these challenges because greater promotion of heathy lifestyle practices in clinical settings effectively motivates and initiates patient behavior change. The 5A Model (assess, advise, agree, assist, and arrange) was developed to provide a framework for clinical counseling with requisite attention to the demands of clinical settings. In this science advisory, we present strategies, based on the 5A Model, that clinicians and other health care professionals can use for efficient lifestyle-related behavior change counseling in patients at all levels of cardiovascular disease risk at every visit. In addition, we discuss the underlying role of psychological health and well-being in lifestyle-related behavior change counseling, and how clinicians can leverage health technologies when providing brief patient-centered counseling. Greater attention to healthy lifestyle behaviors during routine clinician visits will contribute to promoting cardiovascular health.